Morphological variation between two fish populations – phenotypic radiation in a rare case of geographical isolation - Saluceste, Fernanda Biscaíno; Mise, Fábio Teruo; Mayer, Bruna Angelina; Kerniske, Franciele Fernanda; Artoni, Roberto Ferreira; Vitule, Jean Ricardo Simões; Karling, Letícia Cucolo; Affonso, Igor de Paiva (FapUNIFESP (SciELO), 2025)
Abstract Aim We examined the morphology of two populations of the Neotropical Characidae Psalidodon aff. fasciatus from two distinct environments with different selective pressures. One is the single fish population from an isolated lake, hence is deprived of interaction with any other fish species for countless generations. The other shares life-history with several fish. Methods We obtained 10 linear body measurements from 294 specimens from both populations, calculated and compared the ecomorphological indices for each population. Results We found significant distinct morphometry between populations, primarily attributed to the high level of isolation observed in individuals from the isolated population. This population exhibited greater morphological variation, likely due to reduced selection pressure and limited ecological interactions (e.g., absence of other fish species). Conversely, the non-isolated population displayed less morphological variation, possibly as a result of more intense intra- or interspecific interactions, such as competition and predation. Conclusions Considering that allopatry and major factors such as “isolation time” and “ecological interactions” are crucial drivers of evolution, this study highlights a rare case of natural isolation and provides insights for evolutionary investigations on isolated populations, allopatric speciation, and the role of ecological interactions in phenotypic intrapopulation variation. Resumo Objetivo Examinamos a morfologia de duas populações do Characidae Neotropical Psalidodon aff. fasciatus de dois ambientes distintos com diferentes pressões seletivas. Uma é a população única de peixes de um lago isolado, portanto, privada de interação com qualquer outra espécie de peixe por inúmeras gerações. A outra compartilha história de vida com vários peixes. Métodos Obtivemos 10 medidas lineares do corpo de 294 espécimes de ambas as populações, calculamos e comparamos os índices ecomorfológicos para cada população. Resultados Encontramos morfometria significativamente distinta entre as populações, principalmente atribuída ao alto nível de isolamento observado nos indivíduos da população isolada. Esta população exibiu maior variação morfológica, provavelmente devido à reduzida pressão seletiva e às limitadas interações ecológicas (por exemplo, ausência de outras espécies de peixes). Por outro lado, a população não isolada apresentou menor variação morfológica, possivelmente como resultado de interações intra ou interespecíficas mais intensas, como competição e predação. Conclusões Considerando que a alopatria e fatores importantes como “tempo de isolamento” e “interações ecológicas” são impulsionadores cruciais da evolução, este estudo destaca um caso raro de isolamento natural e fornece insights para investigações evolutivas sobre populações isoladas, especiação alopátrica e o papel das interações ecológicas na variação fenotípica intrapopulacional.